2017
DOI: 10.1111/jpc.13568
|View full text |Cite
|
Sign up to set email alerts
|

Injury from falls in infants under one year

Abstract: Fall mechanisms involving infants being dropped by adults, and falls from beds or couches carry the highest clinical burden. These mechanisms should be targets for injury prevention and inform the design of safe equipment and environments for babies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 31 publications
4
26
0
Order By: Relevance
“…In line with previous research on head injuries in infants, most neonatal head injuries were caused by falls at home with the predominant mechanism being falls from care giver's arms . Mulligan et al . found that infants <1 year dropped by care givers were three times more likely to be admitted than infants from other fall types.…”
Section: Discussionsupporting
confidence: 69%
“…In line with previous research on head injuries in infants, most neonatal head injuries were caused by falls at home with the predominant mechanism being falls from care giver's arms . Mulligan et al . found that infants <1 year dropped by care givers were three times more likely to be admitted than infants from other fall types.…”
Section: Discussionsupporting
confidence: 69%
“…Our ndings align well with previously reported studies using administrative datasets and medical record reviews. (4,7,21,22) While some factors we have identi ed have been noted previously, (8,(23)(24)(25) this is the rst to provide this level of detail and identify targets for intervention across the spectrum of fall mechanisms among infants of this age.…”
Section: Discussionmentioning
confidence: 92%
“…(3) Falls are the most common injury mechanism for this age group accounting for almost 50% of all injury hospitalisations. 3The head is the most commonly injured body region (4) and often leads to Traumatic Brain Injuries (TBI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study found that falls and road trauma were the most common mechanisms of head injury for children, particularly falls from playgrounds for children aged 6‐10 years and road trauma for children aged 11‐16 years. Falls typically occurred in children aged <1 year, while being carried or supported by other persons, or from furniture, indicating a need for greater awareness of fall injury prevention and safety amongst caregivers . Falls from playground equipment are a common cause of head injury for children .…”
Section: Discussionmentioning
confidence: 99%